Development of a healthy food and nutrition plan (Malaysia Healthy Food Plan Basket [MHFPB]) for lower-income households in Peninsular Malaysia - Zainal Badari, Shamsul Azahari; Arcot, Jayashree (Malaysian Consumer and Family Economics Association, 2014)
The food assistance program is used to help lower-income households get a nutritious diet. Many developed countries have developed food program to provide nutritional safety for households or individuals to promote good health but not in Malaysia. Thus, the aim of this study was to establish and develop a healthy food and nutrient plan called Malaysia Healthy Food Plan Basket [MHFPB] for lower–income households in Peninsular Malaysia. The development process of this food basket have several stages namely 1) Reference family definition; 2) Food group and serving selection based on Malaysian Dietary Guidelines; 3) Draft of food basket based on the food intake survey; 4) Nutrient analyses and food quantity specification to meet Recommended Nutrient Intake; 5) Definition of food outlet; 6) Food products selection for pricing; 7) Calculation method for MHFPB; 8) Validation of the MHFPB. The results showed that a total of 35 types of foods were included in the MHFPB with 20 types of fresh produce and 15 types of dried produce for reference family members of five. The nutrient content ranged between 88-113% of energy, while for micronutrients, it was quite difficult to achieve 100% of the recommendation, but most of the micronutrient targets for all family members were more than 65%. The weekly cost of foods in MHFPB was RM320.33, with the highest food price was anchovies (RM25.00/kg) and the cheapest food was watermelon (RM1.90/kg). The market survey shows that the increment of 1.5% to 3.3% for two consecutive months, with the price of fish and vegetable groups increase slightly. In conclusion, the food and nutrient plan can be used to supply healthy foods for lower-income households in Peninsular Malaysia, where the price of this plan was considered to be minimum cost to get healthy foods and assumed to be affordable for lower-income families, with a condition that a government give incentives to help this group to buy food. The social food protection program are needed to ensure that nutritious foods can be consumed by lower-income families in Peninsular Malaysia.